(untitled) (Economics and region, 2023)
The article updates the problem of the functioning and development of the insurance market of Ukraine, which needs drastic changes. This is a consequence of the development of the digital economy and the introduction of innovative technologies into all spheres of economic activity through the expansion of e-commerce, e-business, the use of various mobile applications and platforms that are widely Available and provide competitive advantages. It is emphasized that the processes of globalization of financial markets in the world economy have already significantly transformed the relations of insurance companies with agents in the market and prompted the modernization of business models and technological processes. Special attention in the study is given to the analysis of changes in the insurance market of Ukraine, which are taking place against the background of the Covid-19 pandemic and the full-scale military invasion of the Russian Federation. Based on the analysis of the state of Ukrainian insurers, it was concluded that the acquired level of digitalization of the financial space acted as a positive lever for preserving financial stability for Ukrainian insurance companies and allowed them to reshape the vast majority of business processes and communications with clients into a remote format in a short time.